2022
DOI: 10.3390/d14050351
|View full text |Cite
|
Sign up to set email alerts
|

Are the Interactions between Oaks and Pre-Dispersal Seed Predators Retained in Urban Environments? An Analysis of Two Quercus Species in Southern Mexico City

Abstract: As urbanization proceeds, natural ecosystems surrounding cities are transformed, but usually some elements persist, notably trees from forest ecosystems. However, it is still unknown the extent to which isolated trees, immersed in an urban matrix, maintain their interactions with insects that feed on their seeds. In this work we analyzed pre-dispersal seed predation by the two main groups of insects, weevils (Coleoptera; Curculionidae) and moths (Lepidoptera: Tortricidae), whose larvae feed on the acorns of tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Within antagonistic interactions, studies on herbivory rates in cities have shown both increasing and decreasing herbivory with increasing urbanisation, while interactions in which natural enemies are involved were found to be most negatively affected by urbanisation (reviewed by Theodorou, 2022). Past work in urban habitats (e.g., Kozlov et al, 2017;Moreira et al, 2019;Valdés-Correcher et al, 2022) has investigated many types of insect herbivory-including leaf chewing, leaf mining, gall inducing and sap feeding-but seed predation has rarely been evaluated (but see Bode &Gilbert, 2016 andDíaz-Guzmán et al, 2022). In the same way, the parasitism rate of seed predators has not yet been studied in cities.…”
Section: Introductionmentioning
confidence: 99%
“…Within antagonistic interactions, studies on herbivory rates in cities have shown both increasing and decreasing herbivory with increasing urbanisation, while interactions in which natural enemies are involved were found to be most negatively affected by urbanisation (reviewed by Theodorou, 2022). Past work in urban habitats (e.g., Kozlov et al, 2017;Moreira et al, 2019;Valdés-Correcher et al, 2022) has investigated many types of insect herbivory-including leaf chewing, leaf mining, gall inducing and sap feeding-but seed predation has rarely been evaluated (but see Bode &Gilbert, 2016 andDíaz-Guzmán et al, 2022). In the same way, the parasitism rate of seed predators has not yet been studied in cities.…”
Section: Introductionmentioning
confidence: 99%